Зарницы войны: повесть, стихи, поэмы / Эдуард Асадов - Асадов Эдуард Аркадьевич (Воениздат, 1989)
Экземпляры: КХ (20120424) / Инвентарный номер: 944181 / Цена: / Сис.шифр: Р2 / Авт.знак: А 90 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4